Світське життя Луцька в період його перебування у складі Другої речі Посполитої - Малеончук, Галина Олександрівна; Maleonchuk, Halyna O. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті дано характеристику світському життю лучан в 1919 – 1939 рр. Автор, на основі архівних матеріалів, аналізує діяльність громадських організацій та органів державної влади в сфері забезпечення умов для відпочинку та культурного розвитку мешканців міста.

In 1919–1939 Lutck was a part of the Second Polish Republic. The article highlights the high social life of the city in this period. Free time city residents spent in organized social clubs that provide a wide range of services to different national groups of people. Among them are «Ohnisko», «Czech Club», «The Home», «Jugend ferlag». Cultural development while resting was ensured visiting museums, libraries and reading rooms, theaters and movies. The most popular social events in this period were various kinds of evenings which often were a charitable nature. They were organized by public societies and governments. The daily rest of inhabitant of Lutsk in 1919 – 1939 could include a visit cafes and restaurants, walking in city park. Each year, the program of cultural activities consisted with secular and religious events.
High society life of Lutsk during its stay in the Second Polish Republic
Keywords: Луцьк; Lutck; відпочинок; recreation; громадські заходи; social events; клуб; club; кав’ярня; coffee shop